2014
DOI: 10.1126/science.1259512
|View full text |Cite
|
Sign up to set email alerts
|

Bats jamming bats: Food competition through sonar interference

Abstract: Communication signals are susceptible to interference ("jamming") from conspecifics and other sources. Many active sensing animals, including bats and electric fish, alter the frequency of their emissions to avoid inadvertent jamming from conspecifics. We demonstrated that echolocating bats adaptively jam conspecifics during competitions for food. Three-dimensional flight path reconstructions and audio-video field recordings of foraging bats (Tadarida brasiliensis) revealed extended interactions in which bats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 19 publications
0
51
0
Order By: Relevance
“…Territorial behaviors at the roost have been observed for many species, and not coincidentally most examples of singing have been collected at the roost. However, as new tools emerge for recording and tracking the nightly activity patterns of individuals (Cvikel et al 2014) evidence is accumulating that bats do compete for food and defend preferred foraging territories, even if only temporarily or seasonally (Corcoran and Conner 2014). To look more closely at this, we next compare representative examples of the interplay between singing and territorial behaviors from four different bat families.…”
Section: Foraging Ecologymentioning
confidence: 98%
“…Territorial behaviors at the roost have been observed for many species, and not coincidentally most examples of singing have been collected at the roost. However, as new tools emerge for recording and tracking the nightly activity patterns of individuals (Cvikel et al 2014) evidence is accumulating that bats do compete for food and defend preferred foraging territories, even if only temporarily or seasonally (Corcoran and Conner 2014). To look more closely at this, we next compare representative examples of the interplay between singing and territorial behaviors from four different bat families.…”
Section: Foraging Ecologymentioning
confidence: 98%
“…Interestingly, 53% of the SFM calls recorded during feeding activities occurred with the emergence of conspecific echolocation pulses in the terminal phases of insect pursuit, while only 0-2% of other syllable types overlapped with feeding buzzes. Research on Tadarida brasiliensis has demonstrated that SFM signals are used as jamming signals to reduce the foraging success of potential competitors (Ratcliffe et al 2004;Corcoran & Conner 2014). As documented in our spectrograms, SFM exhibits remarkable overlap in fundamental frequency, maximum frequency and downward sweeping portions with feeding buzzes of conspecific bats (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…These contact calls provide evidence for individual signatures, and playback studies demonstrated that bats preferentially responded to the stimuli familiar to them (Arnold & Wilkinson 2011). Corcoran and Conner (2014) confirmed that Mexican free-tailed bats (Tadarida brasiliensis) uttered sinusoidal frequency-modulated (SFM) ultrasonic signals to mediate intraspecific food competition. The SFM calls overlapped temporally and spectrally with feeding buzzes of conspecific bats, and, thus, these calls greatly interfered with the ability of competitors to detect and locate insect prey.…”
Section: Introductionmentioning
confidence: 73%
“…Among these impacts, acoustic masking is especially problematic and has been used to explain the vocal response to noise for many species (e.g. Brumm et al, 2004; Corcoran and Conner, 2014; Francis et al, 2011; Gerhardt and Klump, 1988). The acoustic masking hypothesis states that auditory masking may occur if the target sound and interfering sounds overlap in frequency (Luo et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%